Thermophysical properties - Mendiburu, Andrés Z.; Mariños Rosado, Diego J. [UNESP]; Coronado, Leonardo Geovo; Roberts, Justo J. (Elsevier, 2024)
Nanofluids are promising for industrial applications as they help to enhance heat transfer and thus increase the efficiency of processes that utilize thermal energy. However, to effectively design thermal systems that take advantage of working with nanofluids, thermodynamic and heat transfer models need to be developed. At the same time, the thermodynamic and transport properties of the nanofluids must be determined to provide information for the thermodynamic and heat transfer models. The term thermophysical properties, which is used as the title for this chapter, refers to the thermodynamic and transport properties of the nanofluids. It is important to point out that the determination of the thermophysical properties of nanofluids is still an open area of research, where scientists in both the theoretical and experimental fields are working to improve the currently available models and correlations. Therefore this chapter aims to present the currently available models and correlations that can be applied to estimate the thermodynamic and transport properties of nanofluids. This chapter first presents the means to determine, or obtain, the thermophysical properties of base fluids and nanoparticles as pure substances. Then, the means to estimate the thermodynamic properties of nanofluids are presented by considering the presence of base fluid and nanoparticles in the same thermodynamic system. Finally, this chapter presents the mathematical models available to determine the transport properties of nanofluids considering the concentration of nanoparticles in the base fluid.
Keywords: heat capacity; Nanoparticles; thermal conductivity; thermodynamic properties; thermophysical properties; transport properties; viscosity